Comparison of clinical and laboratory profile of survivors and non‐survivors of SARS‐CoV‐2‐related multisystem inflammatory syndrome of childhood in India: An observational study. (2nd August 2021) - Maheshwari, Anu; Mahto, Deonath; Kumar, Virendra; Gulati, Sameer; Pemde, Harish; Saha, Abhijeet; Mukherjee, Sharmila B; Pandit, Kaveri; Paharia, Konpal; Basu, Srikanta
Abstract : Aim: The SARS‐CoV‐2 pandemic is characterised by multiple reports of paediatric multisystem inflammatory disease or multisystem inflammatory syndrome in children (MIS‐C) with Kawasaki disease‐like features often complicated by myocarditis, shock and macrophage activation syndrome. Certain clinical and laboratory markers may be used to identify high risk cases. Methods: All sequentially admitted patients hospitalised between April 2020 and October 2020, who met the WHO case definition for MIS‐C were included. Data included patient demographic information, presenting symptoms, organ dysfunction and laboratory parameters. SARS‐CoV‐2 infection was diagnosed by nasopharyngeal swab real‐time reverse transcription‐polymerase chain reaction and/or rapid antibody test for SARS‐CoV‐2 as recommended. The clinical and laboratory criteria were compared in the survival and non‐survival groups. Results: A total of 29 patients with MIS‐C were treated during the study period. There were 21 survivors and 8 non‐survivors. The non‐survivors had more neurocognitive and respiratory symptoms along with increased incidence of myocarditis compared with survivors. The serum levels of CPK‐MB, D‐dimer, ferritin and triglyceride were significantly raised in non‐survivors as compared to survivors. Conclusion: The non‐survivor group had higher CPK and greater proportion of children with troponin‐T elevation indicating higher incidence of myocardial injury and necrosis. The D‐dimer, ferritin and triglyceride were also higher in the mortality group, indicating the greater extent of inflammatory damage in this group.